2020
DOI: 10.1111/jfpp.14443
|View full text |Cite
|
Sign up to set email alerts
|

The potential of antimicrobial peptide Hispidalin application in pork preservation during cold storage

Abstract: Hispidalin is a novel antimicrobial peptide and has been largely produced in Pichia pastoris. Considering P. pastoris‐derived Hispidalin has high antimicrobial activity and stability against various conditions, we aim to investigate its potential as a food preservative in pork meat model. Results showed that P. pastoris‐derived Hispidalin had good antioxidant activity and could scavenge against 2,2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonate) radicals, superoxide anions, 1,1‐diphenyl‐2‐picrylhydrazyl radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Hispidalin is a unique AMP derived from the seeds of Benincasa hispida and has been shown to exhibit antimicrobial effects against various microorganisms [126]. Meng et al reported that hispidalin expressed by P. pastorisi was used as a preservative for pork meat [118]. Pork meat treated with 100 µg/mL hispidalin showed bacteriostatic effects during the entire refrigerated storage period.…”
Section: Other Microorganism Sourcesmentioning
confidence: 99%
“…Hispidalin is a unique AMP derived from the seeds of Benincasa hispida and has been shown to exhibit antimicrobial effects against various microorganisms [126]. Meng et al reported that hispidalin expressed by P. pastorisi was used as a preservative for pork meat [118]. Pork meat treated with 100 µg/mL hispidalin showed bacteriostatic effects during the entire refrigerated storage period.…”
Section: Other Microorganism Sourcesmentioning
confidence: 99%
“…Pork is a very popular meat because of its relatively low price, pleasant flavor, tenderness, juiciness and high nutritional value [ 1 ]. However, fresh pork has a shelf life of only a few days due to microbial growth and fat oxidation resulting from the high moisture, fat and protein content of the pork, which causes drip loss (i.e., weight loss), reduced quality and lower commercial value [ 2 ]. In the food industry, the main methods of preserving chilled pork are low temperature, high-voltage electrostatic field, controlled atmosphere and packaging [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compatibility among film components is an essential parameter to be taken care of during the preparation of films. The X-ray diffraction (XRD) technique is well suited for this purpose (Meng et al, 2023). et al (2017), the increase in tensile modulus with higher anthocyanin was due to the enhanced density of film caused by the interaction of anthocyanins with the polymer structure.…”
Section: Biopolymer In Food Packagingmentioning
confidence: 99%